20‐hydroxyeicosatetraenoic acid (20‐HETE) is a pivotal endogenous ligand for TRPV1‐mediated neurogenic inflammation in the skin. (14th February 2022) - Hamers, Alexander; Primus, Christopher P.; Whitear, Charlotte; Kumar, Nitin Ajit; Masucci, Michael; Montalvo Moreira, Shanik A.; Rathod, Krishnaraj; Chen, Jianmin; Bubb, Kristen; Colas, Romain; Khambata, Rayomand S.; Dalli, Jesmond; et al.
Abstract : Background and Purpose: Transient receptor potential cation channel subfamily V member 1 (TRPV1) is localized to sensory C‐fibres and its opening leads to membrane depolarization, resulting in neuropeptide release and neurogenic inflammation. However, the identity of the endogenous activator of TRPV1 in this setting is unknown. The arachidonic acid metabolites 12‐hydroperoxyeicosatetraenoyl acid (12‐HpETE) and 20‐hydroxyeicosatetraenoic acid (20‐HETE) have emerged as potential endogenous activators of TRPV1. However, whether these lipids underlie TRPV1‐mediated neurogenic inflammation remains unknown. Experimental Approach: We analysed human cantharidin‐induced blister samples and inflammatory responses in TRPV1 transgenic mice. Key Results: In a human cantharidin‐blister model, the potent TRPV1 activators 20‐HETE but not 12‐HETE (stable metabolite of 12‐HpETE) correlated with arachidonic acid levels. Similarly, in mice, levels of 20‐HETE (but not 12‐HETE) and arachidonic acid were strongly positively correlated within the inflammatory milieu. Furthermore, LPS‐induced oedema formation and neutrophil recruitment were substantially and significantly attenuated by pharmacological block or genetic deletion of TRPV1 channels, inhibition of 20‐HETE formation or SP receptor neurokinin 1 (NK1 ) blockade. LPS treatment also increased cytochrome P450 ω‐hydroxylase gene expression, the enzyme responsible for 20‐HETE production. Conclusion and Implications: Taken together, our findings suggest that endogenously generated 20‐HETE activates TRPV1 causing C‐fibre activation and consequent oedema formation. These findings identify a novel pathway that may be useful in the therapeutics of diseases/conditions characterized by a prominent neurogenic inflammation, as in several skin diseases.